An algorithm for computation of rainfall water drainage through underground pipeline and canal network affected by tide - Dac, Nguyen Tat (Vietnam Journal of Mechanics, 1996)
It is given in this study an algorithm to calculate flow in underground pipelines connected to canal system affected by tide. The real flow regimes have been taken into computation. Pipelines and canals are considered as one unique system so their interaction has been included in the algorithm. Based on this algorithm a computer program named CONG1093 has been developed and applied to a real problem of rainfall water drainage in Tan Hoa - Lo Gom region, Ho Chi Minh city. The results of application shows practical application of the developed numerical model